Analysis of Economic Growth and Potential Sector Development in the Wajo Regency Region - Nur Syam Hamza (Pustaka Digital Indonesia, 2022)
This study aims to determine the economic sectors that are potential sectors in supporting economic growth in Wajo Regency. The type of research used is quantitative where the researcher collects data in the form of numbers and then processes and analyzes it. The data used in this study is secondary data in the form of PRDB data from business fields in Wajo Regency and South Sulawesi Province in 2015-2019. The data processing technique used to calculate the magnitude of the role of a sector in the region against the sector nationally in this study uses the Location Quention method. Location Quention Method or abbreviated as LQ. The results of the study show that there are 5 sectors that have the potential to support economic growth in Wajo Regency, namely the agriculture, forestry and fisheries sectors, the electricity and gas procurement sector, the wholesale and retail trade sector and car and motorcycle repair, the other service sector and the mining and quarrying sector. However, the mining and quarrying sector is the sector with the highest potential in supporting the economic growth of Wajo Regency, while non-base/non-potential sectors should receive special attention from the Wajo Regency government in order to increase their role so as to support the regional economy .